Aplikasi Amelioran Jerami dan Sekam Padi pada Tanah Gambut terhadap Pertumbuhan dan Produksi Kedelai - Hendra, Hendra; Nelvia, Nelvia; Wardati, Wardati (Jurnal Agro Teknologi Tropika, 2014)
Research applications straw and rice husk as ameliorant on peat soil to improve the growth and production ofsoybean in the peat soil was conducted from April to August 2012, at green house of the Faculty of Agriculture,University of Islamic of Indragiri. The objective was to get the best composition application ameliorant straw and ricehusk on peat soil on the growth and production of soybean. The experiment was used the completely randomized designwith a single factor consisting of 8 treatments (control, 3 tons.ha -1 of AJP, 3 tons.ha-1 of ASP, 3 tons.ha-1 of KJP, 2 tons.ha-1 of KJP + 1 tons.ha-1 of AJP, 2 tons.ha-1 of KJP + 1 tons.ha-1 of ASP, 1 tons.ha-1 of KJP + 1 tons.ha-1 of AJP and 1 tons.ha-1 of KJP + 1 tons.ha-1 of ASP) with 3 replications. Observations of each parameter analysis of variance (F test) and thedifference in treatment was continued with DNMRT (Duncanâs New Multiple Range Test) at 5% level. The results showedgranting ameliorant 3 tons.ha-1 of AJP can improve plant growth in terms of height that 51.16% (145.75 cm), ratio of theroot crown (4.86 g) dry stover weight of 1232.59% (24.12 g) soybean crop production, including number of 272.72% ofpods per plant, number of seeds per plant and seed weight 335.87% 333.23% dry. compared with no treatment.